Gaya Kepemimpinan Kepala Desa Terhadap Peningkatan Partisipasi Masyarakat dalam Pembangunan Desa: Studi pada Desa Cemarajaya - Meliyani; Wanta; Dwi Epty Hidayaty (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The role of the village head is one of the factors influencing the success of village development. Specifically, in the village of Cemarajaya, it is known that the community is still not actively participating in every village development activity. In building the village, the objective of this research is to determine how the village head can encourage community participation in the development of Cemarajaya Village, Cibuaya District, Karawang Regency. This research is qualitative and utilizes data from both primary and secondary sources. Data is collected through techniques such as observation, interviews, and documentation, with triangulation as the analytical tool.